La gansa de los huevos de oro : version de la fabula de Esopo - White, Mark, 1971-; Rojo, Sara, 1973-; Ruiz, Carlos, 1949-; Aesop (Minneapolis : Picture Window Books, 2006)
A farmer learns a lesson in greed when one of his geese begins to lay one--and only one--golden egg each day.
Keywords: Fables; Spanish language materials -- Fiction; Fiction